Precipitation measurements using the quikSCAT radiometer - Kasparis, Takis; Ahmad, Khalil A.; Jones, Wilma L. (My University, 2003)
Microwave brightness temperatures are obtained from the SeaWinds scatterometer on the QuikSCAT satellite. These QuikSCAT Radiometer (QRad) measurements are used to infer instantaneous oceanic rain rates using a statistical retrieval algorithm that is based upon collocated TMI measurements. QRad instantaneous rain rate measurements have been binned in 0.5 hour local time windows onto a 0.5° × 0.5° ocean grid. Also, an average rain rate product is produced, where QRad instantaneous rain rates have been averaged for five-day intervals (pentads) in the 0.5 hour local time windows. The scientific utility of QRad rain measurements is that they provide increased temporal and spatial sampling, which complements that provided by the TRMM Microwave Imager (TMI) and the Special Sensor Microwave Imagers (SSMI's) on the three DMSP satellites. Examples for the year 2000 are presented with corresponding rain rate measurements derived from TMI and SSMI. The results demonstrate that QRad rain measurements agree well with these independent rain observations.
Keywords: Oceanography; Algorithms; Climatology; Radiometers